Respostas bioquímicas, genotóxicas, fisiológicas e histológicas de matrinxã (Brycon amazonicus, Spix; Agassiz 1829) exposto à cipermetrina (Galgotrin®) - Moraes, Fernanda Dias de (Universidade Federal de São Carlos, 2013)
Cypermethrin is a pyrethroid insecticide that reaches aquatic environments over the control of pests in crops and house insects, in urban control of vectors, or directly in fish farms. Galgotrin® is a cypermethrin commercial formulation, namely in this study as cypermethrinbased insecticide (CBI). According to the Ministério da Agricultura Pecuária e Abastecimento , cypermethrin is the most traded insecticide in Brazil. The environmental aquatic contamination by pyrethroids, the adverse effects of such contamination, the lack of national rules to define pyrethroids concentration in water and the commercial importance of matrinxa Brycon amazonicus in Brazil, the study of biochemical and physiological responses of this species exposed to CBI (Galgotrin®) is justified. The goal of this study was to investigate the biochemical, genotoxic, physiological and histothological biomarkers in B. amazonicus exposed to CBI Galgotrin® for 96 hours. Three experiments were conducted: I) acute toxicity, II) sublethal exposure to 20% LC50;96h of CBI for 96 hours and III) sublethal exposure to 20, 40 and 60% LC50;96h of CBI for 96 hours. On the experiment I, the lethal concentration of CBI (Galgotrin®) to 50% of B. amazonicus population was estimated. On the experiment II, the antioxidant metabolism, the lipid peroxidation (LPO), the ionic balance, the hematological profile, the histopathology of gills, and the neurotoxicity were accessed in B. amazonicus exposed to 20% of LC50;96h. On the experiment III, the genotoxicity was accessed by the comet assay in red blood cells and hepatocytes of B. amazonicus exposed to 20, 40 and 60% of LC50;96h. Results of the experiment I indicated that LC50;96h of CBI was 36 μg L-1, extremely toxic to B. amazonicus. Results of the experiment II indicated that the antioxidant metabolism was not enough to counteract the radical oxygen species (ROS) and an oxidative stress occurred in liver and gills of B. amazonicus. Consequently, LPO was observed in these tissues. The plasma sodium and chloride concentrations and the gill Na+/K+- ATPase activity were increased. The red blood cell count (RBCC), the total hemoglobin concentration (total Hb) and the hematocrit (Ht) were increased in the exposed fish. In the gills, the index of histopathological alterations was raised in exposed fish, and some alterations were observed such as hyperplasia, hypertrophy of chloride cell (CC), aneurisms and hemorrhage. The osmoregulatory, hematological and histopathological disorders seemed connected; these adjustments occurred to increase the oxygen and ion uptake. However, some morphological alterations in the gills were due to damages resulted from direct effect of CBI, which is lipophilic. In vitro, CBI was neurotoxic to B. amazonicus; the brain acetylcholinesterase (AChE) activity was decreased up to 65%. In vivo, muscle AChE activity was increased. The results from the experiment III indicated that CBI was genotoxic to red blood cells and hepatocytes of B. amazonicus. The damages on DNA were observed through the comet assay, and the red blood cell presented damages to DNA in a concentrationdependent way. The genotoxicity of CBI (Galgotrin®) could be related to direct effect of the insecticide to DNA and/or to oxidative stress.
Keywords: Peixe; Marcadores biológicos; Estresse oxidativo; Genotoxicidade; Metabolismo; Inseticida piretróide; Biomarcadores; Toxicidade; Piretroide; Biomarkers; Oxidative stress; Genotoxicity; Metabolism; Toxicity; Fish; Pyrethroid; CIENCIAS BIOLOGICAS::GENETICA